Wild hearts can't be broken [videorecording (DVD)] - Anwar, Gabrielle; Schoeffling, Michael; Robertson, Cliff, 1923-2011; Miner, Steve, 1951- (Disney DVD., 2006)
True story of an orphan who is about to become a star diving girl when an accident threatens to destroy her dream.